A Haptic feedback system based on leap motion controller for prosthetic hand application - Hussam K. Abdul-Ameer; Luma Issa Abdul-Kreem; Huda Adnan; Zahra Sami (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Leap Motion Controller (LMC) is a gesture sensor consists of three infrared light emitters and two infrared stereo cameras as tracking sensors. LMC translates hand movements into graphical data that are used in a variety of applications such as virtual/augmented reality and object movements control. In this work, we intend to control the movements of a prosthetic hand via (LMC) in which fingers are flexed or extended in response to hand movements. This will be carried out by passing in the data from the Leap Motion to a processing unit that processes the raw data by an open-source package (Processing i3) in order to control five servo motors using a micro-controller board. In addition, haptic setup is proposed using force sensors (FSR) and vibro-motors in which the speed of these motors is proportional to the amount of the grasp force exerted by the prosthetic hand. Investigation for optimal placement of the FSRs on a prosthetic hand to obtain convenient haptic feedback has been carried out. The results show the effect of object shape and weight on the obtained response of the FSR and how they influence the locations of the sensors.